Innovative methods to increase the effectiveness of teaching the Uzbek language - Yuldashalievna, Usmonova Oyistakhon (International Journal of Psychosocial Rehabilitation, 2020)
What a person learns is that there is an event that is related to the psyche. It is necessary to inculcate the need for language learning in the psyche of the person learning the language, to create a state of need for language learning, to correctly define the purpose of language learning, to increase interest, to imagine the problem. Because language is not just something you learn. It is clear that forced language teaching is also ineffective. However, learning a language also requires special skills and abilities. Language is the cradle of all sciences. It is a necessity in itself that it is not possible to study other sciences as well as specialty sciences without language. Students need to be able to feel this. The process of globalization requires awareness of the achievements of world science in order to improve the development of science. This requires a good knowledge of the native language and foreign languages. It should be noted that the teachings of our ancestors "it is necessary to know not one but four languages" have not lost their relevance today. In particular, it should be borne in mind that finding a solution to the problem of educating a harmoniously developed generation also depends on language. Because the sign of perfection is manifested in language, especially in speech, which is its practical expression.